Halal Thayyiban Branding Strategy Based On Standard Costs Efforts To Increase The Added Value Of Micro-Business Products - Halpiah, Halpiah; Putra, Hery Astika; Pahmi, Saepul (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Community service activities carried out at Alfafa Rasa produce various powdered kitchen spices made from natural Indonesian spices, three years of existence, facing problems in business, where the business experienced slowing growth, products began to be abandoned by consumers, because powdered seasoning products do not have legality such as halal logos, packaging that is not airtight which causes powdered seasonings to clump quickly, so it is necessary to provide product branding assistance that focuses on halal certification, hygienic packaging, standard cost determination, as a strategy that aims to implement product branding with the concept of halalan thoyyiban through obtaining halal certificates, based on standard costs in order to achieve increased product added value and business profits, as well as guarantee a sense of security and comfort in shopping for consumers, implemented using participatory methods, starting with the preparation stage, implementation of activities through education, mentoring, and evaluation, and activities resulting in improvements in product packaging using sachet packaging, and bottles of various variants to provide choices to consumers based on predetermined standard costs, obtaining halal certificates for nine powdered seasoning products, this can increase the selling value of products and business competitiveness as well as increase daily income which previously averaged Rp. 30,000./day becomes an average of Rp. 250,000./day.